2021
DOI: 10.1002/adfm.202009632
|View full text |Cite
|
Sign up to set email alerts
|

Alternative‐Ultrathin Assembling of Exfoliated Manganese Dioxide and Nitrogen‐Doped Carbon Layers for High‐Mass‐Loading Supercapacitors with Outstanding Capacitance and Impressive Rate Capability

Abstract: Manganese dioxide (MnO 2 ) materials have received much attention as promising pseudocapacitive materials owing to their high theoretical capacitance and natural abundance. Unfortunately, the charge storage performance of MnO 2 is usually limited to commercially available mass loading electrodes because of the significantly lower electron and ion migration kinetics in thick electrodes. Here, an alternatively assembled 2D layered material consisting of exfoliated MnO 2 nanosheets and nitrogen-doped carbon layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 88 publications
1
29
0
Order By: Relevance
“…It has been widely demonstrated that doping heteroatoms (such as N, S or P) are an effective approach to regulate physical and chemical properties, including bonding schemes, electronic structure, defects or ion adsorption ability, and thus improve the electrochemical properties of carbonaceous materials [6][7][8]. This strategy has been proven to be effective in energy storage applications (e.g., lithium/ sodium-ion batteries, supercapacitors and oxygen reduction/evolution reaction (ORR/OER)) [9][10][11][12]. In the aspect of K + energy storage systems, heteroatoms-doped carbon fibers [1], graphene [13] or hard carbon [14] exhibit excellent cyclability and rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely demonstrated that doping heteroatoms (such as N, S or P) are an effective approach to regulate physical and chemical properties, including bonding schemes, electronic structure, defects or ion adsorption ability, and thus improve the electrochemical properties of carbonaceous materials [6][7][8]. This strategy has been proven to be effective in energy storage applications (e.g., lithium/ sodium-ion batteries, supercapacitors and oxygen reduction/evolution reaction (ORR/OER)) [9][10][11][12]. In the aspect of K + energy storage systems, heteroatoms-doped carbon fibers [1], graphene [13] or hard carbon [14] exhibit excellent cyclability and rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…One possible means to improve the electrical conductivity and specific area of MnO 2 is to produce nanostructured MnO 2 thin films on conductive carbon-based materials, nanowires, nanosheets, or conductive polymers, for example, MnO 2 /nitrogen-doped carbon, 8 N + MnO 2 @TiC/CC, 9 MnO 2 /CuCo 2 O 4 , 10 and γ-MnO 2 /PANI. 11 In this work, a novel composite structure composed of MnO 2 ultrathin nanosheet is prepared on the TiN nanowire array on a piece of conductive carbon cloth (MnO 2 /TiN/CC) to form a binder-free and flexible positive electrode for supercapacitors as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) transition metal oxides (TMOs) have received considerable attention owing to their distinctive electronic properties as well as high specific surface area and rich active surface sites. 1–6 Orthorhombic phase α-MoO 3 , a stable layered TMO, has been widely used as an anode material for ion batteries ( e.g. , H + , Li + , and Zn 2+ ) and supercapacitors due to its multiple valence states and unique layered structure.…”
Section: Introductionmentioning
confidence: 99%